Antioxidant, antimicrobial and anticancer effects of different extracts from wild edible plant Eremurus spectabilis leaves and roots - Tuzcu, Zeynep; Koclar, Gulden; Agca, Can Ali; Aykutoglu, Gurkan; Dervisoglu, Gokhan; Tartik, Musa; Şahin, Kazım (E-Century Publishing Corp, 2017)
This study was conducted to determine the in vitro antioxidant, antimicrobial, anticancer and apoptotic assays of aqueous and organic extracts of edible Eremurus spectabilis (E. spectabilis) leaves and roots. The total phenolic contents of E. spectabilis extracts were evaluated by the Folin-Ciocalteu method. Aqueous, acetone and ethanol extracts were evaluated for antioxidant potential by the DPPH radical scavenging and lipid peroxidation assays. The antimicrobial activities of E. spectabilis extracts were investigated by the disk diffusion method. Anticancer activities of the extracts were determined by the MTT colorimetric assay in the prostate cancer cell line (PC-3). The WST-1 assay was used to test the extracts on the proliferation of the prostate cancer cell line, PC-3. The radical and hydroxyl scavenging assays and total antioxidant capacity indicated that E. spectabilis possesses potent antioxidant potential. Moreover, E. spectabilis extracts have the potential to inhibit the microbial growth of L. monocytogenes, S. cerevisiae, S. aureus and E. coli. Acetone extract of leaves had the highest phenolic and flavonoid content and antioxidant activity with 3703.25 mu g ascorbic acid/g (dw). Up-regulation of Bax and caspase-3 and down-regulation of Bcl-2 mRNA in treated PC-3 with E. spectabilis indicated mitochondria-mediated apoptosis of PC-3 cells in comparison with control. The results of this study show that E. spectabilis have antioxidant, antimicrobial and antiproliferative effects against prostate cancer cells.
Keywords: Eremurus spectabilis; antioxidant; anticancer activity; prostate cancer